Prevalence and Associated Risk Factors of Childhood Obesity and Overweight in Erbil City, Kurdistan, Iraq: A Household Survey - Mohammed, Sabah Shareef; Shabu, Sherzad Abdulahad (Kurdistan Journal of Applied Research, 2024)
The prevalence of overweight and obesity has increased dramatically during the last three decades. It is estimated that 170 million youngsters (under the age of 18) worldwide are overweight. Obesity is commonly regarded as one of the most significant public health problems of the early 21st century due to its rapid rise and severe public health consequences. According to previous research, the prevalence rate of obesity and overweight increased in Erbil. This study aims to determine the prevalence of childhood overweight and obesity rates in Erbil. This study was a household survey based on a cross-sectional study that was conducted, and a multi-stage sampling strategy was used to choose the study sample. A questionnaire was conducted to collect the data, SPSS was used for analysing the data, and Chi-square (X²), was used to identify any kind of association between different variables in the study, whereas the p-value was considered (0.05). Regarding ethical approval, the study was conducted under the guidelines of the ethical approval research committee in the College of Medicine. In this research, the prevalence rate of obesity and overweight was 30.4%, 7.7% of them were obese, and 22.7% were overweight. The obesity rates between males and females were not different. Lifestyle and habit had an impact on increasing weight gain, though the number of meals, outside eating, fast foods, and snacks between meals were statistically not significant. However, eating without hunger was significant the p-value was (0.008). On the other hand, the children’s habit of using electronic devices, smartphones, and other devices was significant, either using their mobile phone or their parent’s phone. In conclusion, in Erbil city, the prevalence rate of obesity and overweight was dramatically increased, as well as the lifestyle factor that contributed to the development of these conditions, especially among those children exposed to multi-screen devices. According to these results, families have to improve their lifestyles and decrease the use of electrical devices by children.